AN ANALYSIS OF STUDENTS’ FREE WRITING - Rahmi Phonna (Universitas Islam Negeri Banda Aceh, 2014)
Writing contains a compound process to be expressed that entails the writer to pay more attention on linking appropriate words together. Most linguists agree that a writer should attain high level of understanding to pursue the lifelong learning of academic writing pedagogy. This study aimed to analyze the students’ free writing by identifying the category of mistakes that often appear on their writing assignment. 28 free writings were collected, as the main data, from 28 students as the samples for this study. They were then analyzed by using the guidelines of correction symbols from Hogue (1996) and Oshima & Hogue (1999). The results revealed that 11 categories of grammar that often applied incorrectly on the students’ free writing. The misused of verb-agreement (V/A) was the most frequent category occurred, followed by word form (Wf) and Spelling (Sp). The least category of errors identified on the students’ free writing was conjunction (Conj) and wrong word (Ww) categories. Overall, 175 errors from different grammatical conventions were repeated in the students’ free writing.